The 18th International Conference on Experimental Mechanics 2018
DOI: 10.3390/icem18-05373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micro-Structure on the Fatigue Crack Propagation in Bridge Steel

Abstract: Abstract:The use of high strength steels (HSS) allows designing lighter, slenderer and simpler structures with high structural performance. In general, the use of HSS leads to weight reduction of the whole structure, which compensates the higher cost of such a material comparing to the conventional construction steels. Knowledge of the fatigue resistance of material plays the key role during design and maintenance of the bridge structures. This contribution brings a comparison of the fatigue crack growth resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…It is expected that rolling direction corresponds to purposed direction of loading (fatigue cracks initiate and grow perpendicularly to the loading direction), see [9]. Note that previous work on S355 [10,11,12] S355 J2 [13] or S355 J0 [14,15] showed that the fatigue crack propagation rate seems to be independent of the rolling direction and resulting microstructure. Fig.…”
Section: Experimental Data Processing Proceduresmentioning
confidence: 93%
“…It is expected that rolling direction corresponds to purposed direction of loading (fatigue cracks initiate and grow perpendicularly to the loading direction), see [9]. Note that previous work on S355 [10,11,12] S355 J2 [13] or S355 J0 [14,15] showed that the fatigue crack propagation rate seems to be independent of the rolling direction and resulting microstructure. Fig.…”
Section: Experimental Data Processing Proceduresmentioning
confidence: 93%
“…Fatigue progression of the cracks from the edge and from the surface is used as a basis for proposing a system of inspections of details, which tend to be damaged by fatigue [2], [3], [4], sensitivity analysis [5] [6], probabilistic analysis of the S-N field [7], [8] and crack propagation rate [9] etc. The input data are usually material properties [10], [11], [12], [13], [14] and information about boundary conditions-calibration curves [15].…”
Section: Introductionmentioning
confidence: 99%